Hyperion: when walking is fermenting a God - Cavalcante, Marcia; Arango, Diego León (Estudios de Filosofía, 1994)
The first news about the novel Hyperion dates back to the summer of 1792, when Holderlin was already in the seminary in Tübingen. Until the end of the year 1793, the author took care of the elaboration of a first sketch, of which no trace remains. From the beginning of 1794 until the fall, one can speak of the version of the novel to which Holderlin indulged himself during his stay in Waltershausen as tutor to the son of Mrs. von Kalb. It is the famous Fragment of Hyperion, which Schiller published in his magazine Thalia, together with the poem to destiny. From November 1794 to January 1795, Holderlin worked on the metrified version of the novel. From January to August, he continues, still, developing the Hyperion Youth. From August-September to December 1795 he writes the so-called penultimate version, which will be reworked and continued from January to May 1796. From May to December 1796, he prepares the version known as preparation for the definitive version. In 1797 the Cotta editions published, under Schiller's direction, the first volume of the definitive version of the novel and in 1799, the second. In its final version, the novel retained the title of Hyperion or the hermit in Greece.